2014
DOI: 10.5603/kp.a2013.0355
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Gensini score and ST-segment resolution in patients with acute ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: GS-pPCI and high thrombus burden play an important role in predicting inadequate STR in patients with STEMI treated with pPCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
0
6
0
2
Order By: Relevance
“…Although different conclusions have been reached in earlier studies about the use of Gensini score in patients with Abbreviations as in Table 1 STEMI, recently, in their study, Zencirci et al [14] showed that the Gensini score plays an important role in inadequate resolution of ST segment in patients with STEMI undergoing primary percutaneous coronary intervention (PCI) [14]. On the other hand, SYNTAX score was defined initially for stable or unstable angina but then myocardial infarction SYNTAX score was defined for patients with STEMI treated with primary PCI in large-scale studies, and it was shown to be convenient and useful [15].…”
Section: Discussionmentioning
confidence: 87%
“…Although different conclusions have been reached in earlier studies about the use of Gensini score in patients with Abbreviations as in Table 1 STEMI, recently, in their study, Zencirci et al [14] showed that the Gensini score plays an important role in inadequate resolution of ST segment in patients with STEMI undergoing primary percutaneous coronary intervention (PCI) [14]. On the other hand, SYNTAX score was defined initially for stable or unstable angina but then myocardial infarction SYNTAX score was defined for patients with STEMI treated with primary PCI in large-scale studies, and it was shown to be convenient and useful [15].…”
Section: Discussionmentioning
confidence: 87%
“…The left anterior descending (LAD) is the most commonly affected artery in both patient groups. Younger patients frequently present with single-vessel CAD 12,13 , fewer coronary lesions 12 and lower lesion complexity, as estimated by the Gensini score 11 which is a strong predictor of successful restoration of myocardial perfusion 14 as well as short and long-term adverse cardiovascular events 15 16 . Moreover, Gensini score was an independent predictor of long-term mortality in elderly individuals 17 .…”
Section: Coronary Plaque Featuresdifferences Between Elderly and Youn...mentioning
confidence: 99%
“…Hastalar GS'ye göre iki sınıfa bölündü: grup 1 (GS <32 olanlar, hafif KAH) ve grup 2 (GS ≥32 olanlar, ciddi KAH) (12). 11 (10)(11)(12)(13)(14) 11 (10)(11)(12)(13)(14) 0.846…”
Section: Koroner Anjiyografiunclassified
“…Çalışma gruplarının biyokimyasal ve ekokardiyografik özellikleri Tablo 2'de gösterilmektedir. Grup 2'deki hastalarda vWF (140 IU [101-149]'e karşın 120 IU [100-134], P=0.010), BK (10.5[8][9][10][11][12][13][14][15]'e karşın 9.7[7-12.3], P = 0.032), CRP (20 mg/dL'e karşın 11 mg/dL [4-37], P=0.038) ve ESH (20[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]'e karşın 14[10][11][12][13][14][15][16][17][18][19][20][21][22][23], P=0.007) anlamlı olarak daha yüksek idi. Yapılan korelasyon analizinde, gensini skoru ile vWF (r = 0.228, p = 0.007) ve ESH (r = 0.222, p = 0.010) arasında pozitif yönde korelasyon olduğu görüldü (Tablo 3).…”
unclassified